Flett's mean value theorem in topological vector spaces - Robert C. Powers; Thomas Riedel; Prasanna K. Sahoo (International Journal of Mathematics and Mathematical Sciences)
We prove some generalizations of Flett's mean value theorem for a class of Gateaux differentiable functions f:X→Y, where X and Y are topological vector spaces.